Mother’s exclusive breastfeeding behavior: a cross sectional study in Pekanbaru, Indonesia - ., Agrina; Kimura, Rumiko; Tsuda, Akiko (International Journal of Research in Medical Sciences, 2017)
Background: Exclusive breastfeeding (EBF) which is practiced until six months of infant age is one of the most effective ways to reduce infant morbidity and mortality. Indonesian government concerns about mother’s EBF behavior. This study aimed to find the problems of mother’s behavior to give EBF which are influenced by characteristic, knowledge, attitude, and community support including health workers. Methods: A cross sectional study was designed for six hundred and sixty mothers in four public health centers area in Pekanbaru, Indonesia, who have fewer than five years old children as respondents. The study was using questionnaires to collect the data. Results: The average age of respondents was 30.3 years old, 18.9% of them were high educated mothers, 83.6% of them were housewive mothers, and 26.1% of them had high family income. Only 36.1% of the mothers gave EBF until six months while 64.5% of the mothers had limited knowledge, 57.4% of mothers had negative attitude, and 63.5% of mothers had not good behavior for breastfeeding. There were more non EBF housewives mothers than the EBF ones. The majority of the respondents assumed that their breastfeed was insufficient and felt that their babies were still hungry; therefore, they provided formula milk, which was 77.0% and banana, which was 61.6% while 35.8% of them gave 2 kinds of complementary feeding for their babies before six months. Mother’s age, education and family income correlated significantly to EBF practice. Information, values, and emotional support from community also identified as significant aspects for successful EBF practice (p<0.001). Conclusions: Community support plays an important role in succeeding EBF practice for mothers.